Balancing paid work and child care in a slum of Nairobi, Kenya: the case for centre-based child care. Issue 1 (2nd January 2021) - Clark, Shelley; De Almada, Midanna; Kabiru, Caroline W.; Muthuri, Stella; Wanjohi, Milka
ABSTRACT: As a growing number of women across sub-Saharan Africa engage in paid work, they face the challenge of finding suitable child care arrangements. Drawing on survey data from over 1, 200 mothers and in-depth interviews with 31 of these women, we find that mothers living in a slum of Nairobi, Kenya, employ three main strategies to balance their work and child care responsibilities: (1) combine work and child care, (2) rely on kin and neighbours, or (3) use centre-based care. Mothers reported numerous disadvantages to either bringing their children to work or depending on others for child care assistance. In contrast, mothers highlighted several perceived benefits of centre-based child care for themselves and their children, while noting that costs were often prohibitive. These findings suggest that providing affordable centre-based child care could be a key strategy to improving the lives and welfare of women and children living in African slums.